PHYLOGENETIC ANALYSIS OF PROTOZOA AND SISTAN COW’S RUMEN BACTERIA FED WITH FORAGE RATIONS BY MOLECULAR AND LABORATORY METHODS - Pishkar, Gholam; Dehghani, Mohamamd Reza; Sarikhan, Sajjad; Yosf Elahi, Mostafa (Archives of Veterinary Science, 2019)
The present study was conducted to investigate the properties of rumen Microbiome in Sistani cattle by performing molecular experiments to clone the 18S rRNA genes of protozoans, culture rumen bacteria and then sequencing their 16S rRNA gene. Rumen liquid samples were collected from 10 Sistani cattle from the Sistan region, which were kept in a similar feeding group and fed on forage rations, through stomach tubes before feeding in the morning. The protozoa genome was extracted by the ASL buffer of the QiaAmp DNA stool kit (Qiagen), and their 18S rRNA gene was amplified and isolated with specific primers by the PCR method. The quantity and quality of DNA extracted with nanodrop 1000 and electrophoresis on 1% agarose gel, respectively, have been in The 18S rRNA protozoan gene was cloned using the T/A cloning technique in the PTZ plasmid and then the recombinant plasmid was transferred to E. coli.vestigated. The bacteria were cultured with the dependent method and then their 16S rRNA gene was sequenced. Rumen bacteria culture was performed in an anaerobic culture medium using an anaerobic chamber with flexible plastic gloves. After purification, the bacteria were partially studied morphologically. Then the bacterial genome was extracted using a kit, and the 16S rRNA gene was propagated by PCR methods. The sequences have been sent to determine the final structure of the gene for sequencing. In the end, the phylogenetic tree is drawn using the MEGAX software.Investigating of the microbial sequences obtained from the rumen of the cattle showed that the results are somewhat consistent with the results of other researchers in other countries and in other animals, but in some cases, there are significant differences. In this study, the Entodinium genus was the dominant protozoan group in the Sistani cattle’s rumen. In the library, OTUs had a similarity of over 98.5% with the protozoan sequences identified in the database. The results of the culture of bacteria showed Ruminococcus albus, Ruminococcus flavefaciense, Clostridium colinum, Streptococcus equinus and butyrivibrio genus, which had a high similarity of 96.54% with the bacterial sequences identified in the database. Ruminal microbial ecology is very complex. The real scope of this diversity is determined by the use of molecular identification methods for species. The complexity of this diversity is determined by the use of 16S rRNA genes and 18S rRNA genes. Since each microbial species occupies a small area and is found only in some animals.